Functional Analysis of the Chemosensory Protein GmolCSP8 From the Oriental Fruit Moth, Grapholita molesta (Busck) (Lepidoptera: Tortricidae) - Li, Guang-Wei; Chen, Xiu-Lin; Chen, Li-Hui; Wang, Wen-Qiang; Wu, Jun-Xiang (Frontiers in Physiology, 2019)
Chemosensory proteins (CSPs) belong to a family of small water-soluble proteins that can selectively bind and transport odorant molecules in olfactory communication of insects. To date, their definite physiological functions in olfaction remain controversial compared with odorant binding proteins (OBPs). In order to investigate the functions of CSPs in the oriental fruit moth Grapholita molesta, in this study we detected the tissues expression patterns and binding properties of CSP, GmolCSP8. The key binding sites of GmolCSP8 with represent ligand were evaluated using molecular flexible docking, site-directed mutagenesis and ligand-binding experiments. Multiple sequence alignment and phylogenetic analysis showed that GmolCSP8 possess a typical four conserved cysteines motif and shares high sequence identity with some CSP members of Lepidoptera insects. GmolCSP8 was predominantly expressed in the wings and antennae of both male and female adults and may be involve in contact chemoreception. Recombinant GmolCSP8 (rGmolCSP8) exhibited specific-binding affinities to small aliphatic alcohols (C4-12) and had the strongest binding ability to 1-hexanol. The three-dimensional structural of GmolCSP8 was constructed with the structural of CSPsg4 as a template, the site-directed mutagenesis and ligand-binding experiments confirmed that Thr27 is the key binding site of GmolCSP8 bind to 1-hexanol owing this residue can form hydrogen bond with the oxygen atom of hydroxyl group in 1-hexanol, and Leu30 also play an important role in bind to 1-hexanol. We further found that the pH values were significantly affected the binding affinities of rGmolCSP8 to ligand, revealing the ligand-binding and -release of this protein is related to a pH-dependent conformational transition. Based on the above experimental results, we infer that GmolCSP8 may participate in the recognition and transportation of 1-hexanol and other small aliphatic alcohols.